Three essays on oil prices and economic activity in Turkey - Torul, Orhan. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This thesis consists of three essays analyzing the effects of oil prices on the Turkish economy. In the first essay, I investigate the relationship between oil prices and real aggregate output of a small open economy, Turkey. Parallel to the results for developed economies in the literature, I first report for Turkey that the negative response of real output to oil price increases have diminished since the early 2000s. Yet, when I incorporate global liquidity conditions, I unveil that the negative impact of oil price changes is significant even in the post-2000 period. In the second essay, I empirically investigate the impact of shocks to world crude oil prices on retail gasoline prices in Turkey. First, I report that domestic prices respond significantly to increasing world crude oil prices, but not to decreases. I argue that the source of observed asymmetry is mainly attributable to government price setting policy. I also claim that rather than smoothing the impact of volatility in world crude oil prices on retail gasoline prices, the Turkish fiscal authorities attempt to maximize tax revenue from gasoline. In the third essay, I investigate the relationship between oil prices and the manufacturing sector of Turkey. I take into account unique features of Turkey, and incorporate global liquidity and domestic finance conditions, along with real exchange rate dynamics in my model. I report that while oil price increases fail to impede aggregate manufacturing growth, they robustly impede production growth of some of the sub-sectors.
Keywords: Petroleum products -- Prices -- Turkey.